Kawasaki Disease: A Never-ending Story? - Alessandro Cavalcanti Lianza; Maria de Fátima Rodrigues Diniz; Karen Saori Shiraishi Sawamura; Carolina da Rocha Brito Menezes; Isabela de Sousa Lobo Silva; Gabriela Nunes Leal (European Cardiology Review)
The most severe complication of Kawasaki disease, an inflammatory disorder of young children, is the formation of coronary artery aneurysms. It is known that patients with coronary artery aneurysms, particularly those with medium and large lesions, have a higher risk of future major cardiovascular events. In contrast, there is a lack of data on the cardiovascular status in long-term follow-up for Kawasaki disease patients without coronary involvement or with self-limited coronary artery aneurysms, resulting in most patients being discharged after 5 years. Even though some paediatricians may believe these patients should not be followed at all, studies indicating a dysfunctional endothelium show the need for further investigation. Consequently, a review of the most significant aspects of Kawasaki disease, and the necessity of correctly identifying, treating and monitoring these patients, particularly those with a higher risk of complications, was conducted.